1972
DOI: 10.1111/j.1532-5415.1972.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociopsychological Obstacles to L‐Dopa Therapy That May Limit Effectiveness in Parkinsonism

Abstract: Chronic illness produces changes in patients' self-conceptions and social relationships which may impair their level of functioning. L-dopa therapy is particularly relevant t o patients ill for some time with a disease believed by themselves and their associates t o be chronic. In parkinsonian patients, therefore, the effect of L-dopa on their level of functioning, as distinct from their symptoms, is likely to be inhibited by some of the social and psychological concomitants of chronic illness. The literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Ultimately, those questions can be resolved only through replication, but it is important to observe that the descriptions of patients with mild to moderate physical impairment (Clusters I and II) are consistent with results from studies of other chronically ill patients (Mendelsohn, 1979;Nerenz & Leventhal, 1983;Singer, 1974aSinger, , 1976Taylor et al, 1984). The replicability of the other two clusters, depressed and misunderstood (Cluster III) and passive and resigned (Cluster IV), is more questionable, although anecdotal and clinical data are consistent with the findings reported in the present research (Hyman, 1972;Morris, 1982;Paulson, 1981). Finally, it should be noted that the convergence of the Q-sort data and the self-report data speak to the meaningfulness, if not the replicability, of the clustering in this sample.…”
Section: Discussionsupporting
confidence: 90%
“…Ultimately, those questions can be resolved only through replication, but it is important to observe that the descriptions of patients with mild to moderate physical impairment (Clusters I and II) are consistent with results from studies of other chronically ill patients (Mendelsohn, 1979;Nerenz & Leventhal, 1983;Singer, 1974aSinger, , 1976Taylor et al, 1984). The replicability of the other two clusters, depressed and misunderstood (Cluster III) and passive and resigned (Cluster IV), is more questionable, although anecdotal and clinical data are consistent with the findings reported in the present research (Hyman, 1972;Morris, 1982;Paulson, 1981). Finally, it should be noted that the convergence of the Q-sort data and the self-report data speak to the meaningfulness, if not the replicability, of the clustering in this sample.…”
Section: Discussionsupporting
confidence: 90%
“…Such experiences extended to public situations as studies have found that participants with PD experienced other people staring at them [63] or directly expressing irritation at PD symptoms [69]. Furthermore, people with PD movement difficulties can be viewed as less socially desirable [70], and this may manifest as hurtful comments or avoidance of people with PD [71]. …”
Section: The Stigma Of Movement Difficultiesmentioning
confidence: 99%
“…Indeed, some qualitative studies have explored the concept of self identity in PD (e.g., [62, 71]), and participants have described the challenges of living with PD and how it affects their sense of self and their social roles. Charmaz [87] suggested that people with chronic illness experience discreditation of their self identity, which can be influenced by stigmatising and disabling societal views of illness.…”
Section: The Psychoemotional Impact Of Stigma Surrounding Pdmentioning
confidence: 99%
“…Only a small group of studies have been designed to explore how Parkinson patients perceive their disease and adapt to it (Hyman, 1972; Paulson, 1981; Singer, 1973, 1974a, 1974b, 1976). Of these, Singer's work alone is a systematic study; Paulson and Hyman provided only anecdotal clinical observations.…”
Section: Current Literature: 1970 To the Presentmentioning
confidence: 99%